The transcendental and the mundane Chinese cultural values in everyday life - Xu, Zhuoyun 1930- (The Chinese University of Hong Kong Press, 2022)
"Through investigation of Chinese cultural ideals and life practices, Prof. Cho-yun Hsu constructs an original portrait of Chinese spiritual life. Apart from focusing on the exalted subtleties of the scholarly elite, Prof. Hsu pays more attention to the everyday people's cultural idea. By examining their daily practices (including eating, living, medical practices, poems, songs, art, and literature) and "collective memory" such as legends, he seeks to clarify Chinese ideas concerning the universe, human life and nature, from traditional times down to the present day. Different from Judeo-Christian tradition centered on "God," the spiritual life of the Chinese people develops around ideas of being "human," and thus cultivating an interactive relationship between man, time, and space. Cho-yun Hsu considers the mode and direction of Chinese culture will impact the future of the entire world. Based on his observation, Western civilization represented by Europe and America nowadays is on the verge of a great change. The problems they are facing, including various crises of alienation and separation from nature, are, in terms of their basic origins, problems for which Western civilization lacks the resources to arrive at a solution. Thus, Chinese culture centered on the man and on the idea of intimate, interdependent relations between man and nature, might offer another solution. It is expected that, by integrating its features into modern civilization, Chinese culture can continue to prosper and be of benefit to the future of the world." -Amazon.com
Translation of: Zhongguo ren de jing shen sheng huo
Keywords: Geschichte; Kultur; Religion; China; Philosophy, Chinese; China / Civilization; Civilization